Exposure of lung fibroblasts to PM2.5 and lead (Pb) induces fibrosis and apoptosis in alveolar epithelial cells via a paracrine effect - Jung-Yun Choi; Minje Kang; Ji-Hye Jung; Woo Jin Kim; Hyo-Seon Yang; Kyuhong Lee; Jooyeon Lee; Se-Ran Yang; Chin Kook Rhee; Seok-Ho Hong (Ecotoxicology and Environmental Safety)
Exposure to fine particulate matter (PM2.5) and heavy metals (HMs) in the air is closely associated with the incidence and exacerbation of pulmonary fibrosis. Although the specific responses of alveolar epithelial cells (AECs) and lung fibroblasts to PM2.5 or HM exposure have been well defined, the cellular responses of lung fibroblasts to PM2.5 or HM exposure and the subsequent interactions with AECs remain poorly investigated. In this study, we demonstrated that human lung fibroblasts exposed to PM2.5 or lead (Pb) induced fibrotic changes and apoptosis in AECs. Lung fibroblasts exposed to PM2.5 induced fibrotic changes in AECs via a paracrine action. We further evaluated the detrimental effects of four HMs (cadmium, lead, arsenic, and manganese) present at the highest levels in the ambient air of South Korea, and investigated their paracrine effects on AECs. We found that long-term (14 passages) exposure to these HMs negatively affected the growth, migration, and survival of lung fibroblasts. Notably, manganese (Mn) significantly upregulated the expression of fibrotic markers with the activation of extracellular signal-regulated kinase (ERK) signaling in lung fibroblasts. However, treatment with conditioned medium (CM) collected from Mn-treated lung fibroblasts did not induce fibrotic changes in AECs. Interestingly, CM from Pb-treated lung fibroblasts significantly upregulated markers for fibrosis and apoptosis in AECs via activation of the ERK signaling pathway. These results suggest that understanding interactions between fibroblasts and AECs may provide useful strategies against PM or HM-induced injuries in alveolar tissue.